Comparison of External Focus Instructions Based on Mechanics and Performance in the Vertical jump: Examining the constrained action hypothesis - Seyyed Fardin Qeysari; Somayeh Emamrezaii; Amineh Eslamizad; Seyyed Kamal Qeysari (Biyumikānīk-i varzishī, 2023)
Objective In some situations, however, the goal of the skill is to correct movement mechanics, and in these specific scenarios, external focus instructions should be specific to mechanics. External focus instructions based on performance do not have a positive effect on motion mechanics. The purpose of this study was to investigate the effect of external focus instructions based on mechanics and performance in the vertical jump movement: Examining the constrained action hypothesis. Methods Twelve male professional volleyball players (average age 24.0±1.92 years; average weight 73.5±8.7 kg) voluntarily participated in this research. Subjects performed the vertical jump movement with all their strength in two external focus situations (1- performance-based external focus, 2- mechanics-based external focus) on the force plate. In order to investigate the electromyography activity of the right abdominal muscle, an electromyography device was used, which was simultaneous with the force plate device in terms of time. The ground reaction force data based on time by the force plate were used to obtain the different time phases of the vertical jump and to calculate the jump height. Results The results of the paired t-test showed that the jump height in the performance-based external focus condition was significantly higher than the mechanics-based external focus condition (P<0.001). Also, the focus of external attention based on mechanics compared to the focus of external attention based on performance caused a significant increase in the electrical activity of the right abdominal muscle during the concentric phase (P<0.001). However, there was no significant difference in the eccentric phase of the electrical activity of the right abdominal muscle between the two conditions (P=0.233). Conclusion These results indicate that performance-based external focus instructions lead to greater automaticity of movement and improved performance. However, it is not useful for improving movement mechanics, and for this purpose, external focus instructions based on movement mechanics should be used.